Slaughterhouse zoonoses: Are workers reservoirs of zoonotic disease? - Cook, Elizabeth A.J.; Gibbons, C.L.; Bronsvoort, B.M. de C.; Kariuki, S.; Fèvre, Eric M. (International Livestock Research Institute, 2012)
Slaughterhouse workers are considered a high risk group for zoonotic disease due to increased contact with animals, animal products and excreta. Globally, slaughterhouse workers have been shown to have an increased seroprevalence to zoonotic pathogens, though no such studies exist in Kenya. Slaughterhouse workers may also act as reservoirs of these zoonotic organisms and asymptomatic carriage of pathogenic bacteria has been demonstrated. This study aimed to determine the carriage of enteropathogens in slaughterhouse workers in rural western Kenya and to determine if there was asymptomatic carriage of Staphylococcus aureus specifically Methicillin Resistant S. aureus (MRSA). This study was conducted in the Lake Victoria Crescent region of western Kenya. Five hundred slaughterhouse workers from this region were asked a comprehensive questionnaire regarding risk factors for zoonotic disease, faecal samples were collected for examination and culture and a nasal swab was cultured for S. aureus. This study reports on the seroprevalence of Salmonella spp, Shigella spp, pathogenic Escherichia coli and Campylobacter spp. in these individuals as well as reporting the nasal carriage of S. aureus and MRSA. This is the first community based study regarding S. aureus and MRSA in Kenya. The asymptomatic carriage of these organisms in slaughterhouse workers highlights a reservoir that may be important in the dissemination of these pathogens. The study further comments on the risk factors for infection with these pathogens and suggestions are made for simple hygiene interventions that can reduce disease in slaughterhouse workers and dissemination to the wider community